2019
DOI: 10.3389/fphys.2018.01947
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Cosine Transform for the Analysis of Essential Tremor

Abstract: Essential tremor (ET) is the most common movement disorder. In fact, its prevalence is about 20 times higher than that of Parkinson's disease. In addition, studies have shown that a high percentage of cases, between 50 and 70%, are estimated to be of genetic origin. The gold standard test for diagnosis, monitoring and to differentiate between both pathologies is based on the drawing of the Archimedes' spiral. Our major challenge is to develop the simplest system able to correctly classify Archimedes' spirals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Recently, many works have focused on providing digital cognitive and motoric function self-assessment tests on electronic consumer devices, such as smartphones [8], tablets [9], and dedicated graphical tablets [10]. Commonly implemented tests include Archimedes spiral drawing tasks [11][12][13][14][15][16][17], finger tapping [9], freehand drawing tasks [17], and tracing tasks [12,17].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many works have focused on providing digital cognitive and motoric function self-assessment tests on electronic consumer devices, such as smartphones [8], tablets [9], and dedicated graphical tablets [10]. Commonly implemented tests include Archimedes spiral drawing tasks [11][12][13][14][15][16][17], finger tapping [9], freehand drawing tasks [17], and tracing tasks [12,17].…”
Section: Related Workmentioning
confidence: 99%
“…Commonly implemented tests include Archimedes spiral drawing tasks [11][12][13][14][15][16][17], finger tapping [9], freehand drawing tasks [17], and tracing tasks [12,17]. The methods used to analyze the collected spatiotemporal finger tapping, finger drawing, or pen path data include statistical analysis [11,12,15], discrete cosine transform (DCT) features [10], entropy, and fractal dimension analysis [13].…”
Section: Related Workmentioning
confidence: 99%
“…As part of a larger cross-sectional study for characterizing ET, our group has previously demonstrated how nonlinear biomarkers from handwriting (Lopez-de-Ipina et al, 2016 , 2018 ) can be used as a tool for developing an automatic classification of ET toward early diagnosis. Additionally, Solé-Casals et al ( 2019 ) demonstrated how new biomarkers from drawings and handwriting can be utilized from discrete cosine transformations (DCT).…”
Section: Introductionmentioning
confidence: 99%
“…This overactivity could appear in motor control trajectory, pressure, and/or their combinations. Thus, tracking these subtle differences in phenotype could be useful for early detection and correlation with brain structural changes ( Figure 1 ; Lopez-de-Ipina et al, 2018 ; Solé-Casals et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Simple pen and paper tests are often performed in the clinic, both as a diagnostic aid for ET and as a rough measure of severity for monitoring purposes [4]. Computerized methods using digital tablets [5]- [12] or wearable sensors [13]- [17] have potential as sensitive and quantitative assessments of writing and drawing in ET. This could augment, or even outperform, the standard clinical tools for tremor grading, and would be of particular use in clinical trials of pharmacological treatments of ET.…”
Section: Introductionmentioning
confidence: 99%